2022
DOI: 10.1007/s12520-022-01678-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-isotopic study of the earliest mediaeval inhabitants of Santiago de Compostela (Galicia, Spain)

Abstract: Santiago de Compostela is, together with Rome and Jerusalem, one of the three main pilgrimage and religious centres for Catholicism. The belief that the remains of St James the Great, one of the twelve apostles of Jesus Christ, is buried there has stimulated, since their reported discovery in the 9th century AD, a significant flow of people from across the European continent and beyond. Little is known about the practical experiences of people living within the city during its rise to prominence, however. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…quantity and information because of the subjectivity of the authors, who usually focused on members of the clergy and/or nobility (Andrade Cernadas, 2014). Stable isotope analysis has frequently been used in medieval contexts to explore varying reliance on different crops (Alexander et al, 2015), animal protein (Jiménez-Brobeil et al, 2016), and aquatic resources (López-Costas and Müldner, 2018), dietary variations between different socio-economic status (Jordana et al, 2019;Lubritto et al, 2017;MacKinnon et al, 2019;Martínez-Jarreta et al, 2018;Pérez-Ramallo et al, 2022a;Jiménez-Brobeil et al, 2020), and to identify local and non-local individuals (Guede et al, 2017(Guede et al, , 2018López-Costas et al, 2021;Pérez-Ramallo et al, 2022b). Here, we analyse 82 human individuals and 42 faunal specimens from 8 different archaeological sites in a relatively small area in the northeast of the Iberian Peninsula that corresponds to the current regions of Navarre and Aragon (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…quantity and information because of the subjectivity of the authors, who usually focused on members of the clergy and/or nobility (Andrade Cernadas, 2014). Stable isotope analysis has frequently been used in medieval contexts to explore varying reliance on different crops (Alexander et al, 2015), animal protein (Jiménez-Brobeil et al, 2016), and aquatic resources (López-Costas and Müldner, 2018), dietary variations between different socio-economic status (Jordana et al, 2019;Lubritto et al, 2017;MacKinnon et al, 2019;Martínez-Jarreta et al, 2018;Pérez-Ramallo et al, 2022a;Jiménez-Brobeil et al, 2020), and to identify local and non-local individuals (Guede et al, 2017(Guede et al, , 2018López-Costas et al, 2021;Pérez-Ramallo et al, 2022b). Here, we analyse 82 human individuals and 42 faunal specimens from 8 different archaeological sites in a relatively small area in the northeast of the Iberian Peninsula that corresponds to the current regions of Navarre and Aragon (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that individuals belonging to the Christian social elite of the time (10th-12th centuries CE) exhibited higher stable nitrogen isotope values (δ 15 www.nature.com/scientificreports/ Peninsula 17,32,33 . However, a significant number of studies also observed no differences 4,29,[34][35][36] . Still, the fact that we could only analyse one female individual inhibits any comprehensive comparison based on sex.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we should approach this interpretation with www.nature.com/scientificreports/ caution until further analysis of local plants and freshwater fish can provide a more reliable model. In addition, the impact of an individual's geographical origin on these dietary patterns remains uncertain and necessitates further analyses, including studies using 87 Sr/ 86 Sr, δ 18 O, and δ 34 S proxies 34,35,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a chemical level, the elements in the bones and teeth of these individuals can provide important information on their dietary and mobility patterns. Stable isotope analysis of carbon (δ 13 C) and nitrogen (δ 15 N) has become an increasingly common practice in archaeological studies of the diets of humans and animals living in the past [4][5][6][7] and more recently there is an expanding corpus of isotope studies focused on medieval Iberia although, to date, many more have been focused on medieval Spain [8][9][10][11][12][13][14][15][16][17][18] than on Portugal [19][20][21][22]. Published data on the mobility of medieval Iberian populations is even more scarce than dietary research, or indeed scarcer than mobility studies for other time periods in Iberia.…”
Section: ) Introductionmentioning
confidence: 99%